9y=3x-(x-1),4(x+y)-(2x+4)=8y
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/01 23:03:33
9y=3x-(x-1),4(x+y)-(2x+4)=8y9y=3x-(x-1),4(x+y)-(2x+4)=8y9y=3x-(x-1),4(x+y)-(2x+4)=8y解9y=3x-(x-1)2x-9
9y=3x-(x-1),4(x+y)-(2x+4)=8y
9y=3x-(x-1),4(x+y)-(2x+4)=8y
9y=3x-(x-1),4(x+y)-(2x+4)=8y
解
9y=3x-(x-1)
2x-9y+1=0 ①
4(x+y)-(2x+4)=8y
2x-4y-4=0 ②
②-①得:
5y-5=0
∴y=1
将y=1代入①得:2x-9+1=0
∴x=4
∴方程的解为:x=4,y=1
整理:
9y=2x+1
2x-4=4y
2式变为2x=4y+4代入1式:
9y=4y+4+1
y=1
再代入得x=4
9y=3x-(x-1),4(x+y)-(2x+4)=8y
3(x+y)-2(x-y)=11 4(x+y)+3(x-y)=9
4(x-y)-3(x-y)=9 5(x-y)+2(x-y)=11
{3(x+y)+3(y+x)=1,3(x+y)+4(y-x)=-1
{3(x+y)-4(x-y)=4 {x+y/2 + x-y/6=1
(x-y)/4+(x+y)/5=1/4 (x+y)/9-(x-y)/3=//2(x-y)/4+(x+y)/5=1/4(x+y)/9-(x-y)/3=//2
x+y+2(-x-y+1)=3(1-y-x)-4-(y+x-1),x+y=?
解方程组:{4/x+y+6/x-y=3 9/x-y-1/x+y=1}
解方程组{4/x+y+6/x-y=3, 9/x-y-1/x+y=1
解二元一次方程 {3(x+y)-4(x-y)=-9 x+y/2+x-y/6=1
化简[(3x+4y)^2-(2x+y)(2x-y)+(-x+y)(5x-y)]除以-2y,其中x=-1,y=1
先化简 再求值 (2x-y)(y+x)-(x-2y)(2y+x)-(-3y+x)^2其(√x+1)+y^2+4=-4y
已知x-y=1,求[(x+2y)²+(2x+y)(x-4y)-3(x+y)(x-y)]÷y的值
已知x-y=1,求[(x+2y)^2+(2x+y)(x-4y)-3(x+y)(x-y)]除以y的值大神们帮帮忙
(x-y) (x-2y)+(x+2y) (x-3y)-2(x-3y) (x-4y)=
x²/xy-x/y 3x/4x+y - x-2y/4x+y (1-y/y+x)÷x/y²-x²
若(-x+6):(x-y):(4x+y)=3:14:1,求x+y
若(-x+6):(x-y):(4x+y)=3:14:1,求x+y